Multi-objective task offloading algorithm for mobile cloud computing - Fuhong SONG; Huanlai XING; Wei PAN (物联网学报)
Mobile devices with limited computing power and resources can offload intensive tasks to the cloud for execution,thus improving the computing capacity of mobile devices and reducing battery energy consumption.However,the existing researches cannot properly balance the application finish time and energy consumption of the mobile terminal when offloading tasks.An MOEA/D based algorithm was proposed to optimize the application finish time and energy consumption,and dynamic voltage frequency scaling technology was introduced into the MOEA/D to adjust the CPU clock frequency of mobile devices to further decrease the energy consumption without increasing the application finish time.The simulation results demonstrate that the proposed algorithm outperforms a number of existing algorithm in terms of the multi-objective performance.